2022
DOI: 10.1128/mbio.03595-21
|View full text |Cite
|
Sign up to set email alerts
|

MgrB-Dependent Colistin Resistance in Klebsiella pneumoniae Is Associated with an Increase in Host-to-Host Transmission

Abstract: The biological cost associated with colistin resistance in Klebsiella pneumoniae was examined using a murine model of K. pneumoniae gut colonization and fecal-oral transmission. A common mutation resulting in colistin resistance in K. pneumoniae is a loss-of-function mutation of the small regulatory protein MgrB that regulates the two-component system PhoPQ.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 67 publications
(104 reference statements)
1
14
0
Order By: Relevance
“…However, a high variety of other non-described mutations were detected, supporting the urgent need for reliable genotypic-phenotypic correlations to explain colistin resistance mechanisms (51). Such a variety and frequency of chromosomal mutations in ColR-Kp detected in different studies and environments (26, 43, 50, 51) suggest they could play a role in adaptive features other than colistin resistance (e.g., mgrB inactivation in environmental K. pneumoniae survival and transmission; phoPQ or pmrB mutations in chlorhexidine tolerance) (52)(53)(54). Also, some of these mutations do not confer significant biological cost (55,56) which may explain the occurrence of colistin-resistant mcrnegative K. pneumoniae long after colistin withdrawal.…”
Section: Discussionmentioning
confidence: 91%
“…However, a high variety of other non-described mutations were detected, supporting the urgent need for reliable genotypic-phenotypic correlations to explain colistin resistance mechanisms (51). Such a variety and frequency of chromosomal mutations in ColR-Kp detected in different studies and environments (26, 43, 50, 51) suggest they could play a role in adaptive features other than colistin resistance (e.g., mgrB inactivation in environmental K. pneumoniae survival and transmission; phoPQ or pmrB mutations in chlorhexidine tolerance) (52)(53)(54). Also, some of these mutations do not confer significant biological cost (55,56) which may explain the occurrence of colistin-resistant mcrnegative K. pneumoniae long after colistin withdrawal.…”
Section: Discussionmentioning
confidence: 91%
“…For the PhoQP/MgrB system from K. pneumoniae this idea has been recently proposed. Bray et al (2021) [73] demonstrated that loss of MgrB in colistin resistant- K. pneumoniae is accompanied by compromised gastrointestinal colonisation efficacy. Like our results, this study too reported the overproduction of RpoS in mgrB -deficient K. pneumoniae .…”
Section: Discussionmentioning
confidence: 99%
“…Like our results, this study too reported the overproduction of RpoS in mgrB -deficient K. pneumoniae . However, the authors reported that RpoS overproduction was beneficial in a model for pathogen transmission [73]. Thus, life-history and growth context are both likely to have a strong influence on how deregulation of gene expression translates to organismal fitness.…”
Section: Discussionmentioning
confidence: 99%
“…When a bacterium becomes resistant to colistin, it can also simultaneously become impervious to components of the host"s defense system, such as lysozymes and cationic antimicrobial peptides (CAMPs), principally as they act on the same target of polymyxins, hence the main mechanism of resistance of K. pneumoniae is genetic regulation of LPS formation, particularly lipid A (31) .…”
Section: Polymyxin Resistancementioning
confidence: 99%